Analisis faktor-faktor penyebab rendahnya akhlak siswa di MI Muhammadiyah Derasan Andong Boyolali tahun pelajaran 2022/2023 - Ribut Santoso; Joko Subandono; Meti Fatimah (At Turots: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to find out the analysis of the teacher's strategy in increasing the moral values of MIM Derasan Andong Boyolali students. This research uses a descriptive qualitative approach, conducted at MIM Derasan Andong Boyolali. Methods of data collection using observation methods, interview methods, and documentation methods. The data validation technique uses triangulation techniques. Analytical techniques with interactive analysis techniques which include data reduction, data presentation, and conclusion drawing. The results of the data analysis concluded that at MIM Derasan Andong Boyolali, through the exemplary method, the habituation method, the attention method, the warning method, and through subjects, namely: crafts, namely making tablecloths in groups, social values are cooperation and cohesiveness, social studies, namely remembering the services of the heroes and social problems, the social value is togetherness, Civics is freedom of organization and joint decisions, the social value is cooperation, and cohesiveness, responsibility and so on, Indonesian is writing about heroic stories, the social value is willing to sacrifice Penjasorkes through football games and kasti, the social value of cooperation, helping and cohesiveness is the Aqidah Akhlaq, namely adab associating with older people, the social value is harmony and togetherness, Fiqh, namely Infaq and praying five times a day, namely togetherness.